Formulation And Physical Stability Of Hair Tonic Ethanol Extract Of Katuk Leaves (Sauropus Androgynous (L.) Merr) - Arif, Muhammad; Nurbaiti; Rahmawati, Ayu; Oriendhini, Salsa (The Journal Of Pharmacy, 2023)
Katuk leaves (Sauropus androgynus (L.) Merr) contain provitamin A and vitamin E, flavonoid, and ascorbic acid, which help hair growth. This study aims to determine the stability level of hair tonic preparations of ethanol extract from katuk leaves. The method used in this study is the cycling test method. This study made a hair tonic formulation with 2.5% ethanol extract of katuk leaves with a variation of 96% ethanol concentration of 35 ml and 10 ml. The stability parameters tested include organoleptic, pH, viscosity, specific gravity, and homogeneity. The pH test results range from 4.4 to 5.3; this pH value follows the Indonesian National Standard (SNI). The viscosity test ranged from 0.59-0.69; this pH value complies with the Indonesian National Standard (SNI). The specific gravity test results ranged from 1.02-1.04, and this particular gravity value was not the theory of specific gravity of hair tonic less than 1. The homogeneity test results showed that the hair tonic experienced precipitation and was not homogeneous. Furthermore, the hedonic test showed that the panellists preferred the negative control preparation, then the hair tonic preparation of katuk leaf ethanol extract with 96% ethanol variation of 60 ml and finally, the hair tonic preparation of katuk leaf ethanol extract with 96% ethanol variation of 35 ml.